2021
DOI: 10.1007/s10561-021-09964-2
|View full text |Cite
|
Sign up to set email alerts
|

The estimated risk of SARS-CoV- 2 infection via cornea transplant in Canada

Abstract: In late 2019 the respiratory illness, Corona Virus Disease-19 caused by the SARS-CoV-2 virus emerged in China and quickly spread to other countries. The primary mode of transmission is person-to-person via respiratory droplets. SARS-CoV-2 has been identified in conjunctiva. Transmission by cornea transplant has not been reported but is theoretically possible. We aimed to estimate the possible risk of transmission in Canada via cornea transplant during the first wave of the pandemic, and the potential risk redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…[ 53 54 55 ] Whereas, a recent analytical study showed a low risk of infection through corneal transplant. [ 56 ] Furthermore, several studies showed the existence of SARS-CoV2 in the conjunctival discharges and tears, which are potential ways for spreading the virus into the nasopharynx or eye contact. [ 2 57 58 59 60 61 62 63 64 65 ] However, according to a recent systemic review, no-cut clinical evidence demonstrated that eyes are a transmission pathway for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…[ 53 54 55 ] Whereas, a recent analytical study showed a low risk of infection through corneal transplant. [ 56 ] Furthermore, several studies showed the existence of SARS-CoV2 in the conjunctival discharges and tears, which are potential ways for spreading the virus into the nasopharynx or eye contact. [ 2 57 58 59 60 61 62 63 64 65 ] However, according to a recent systemic review, no-cut clinical evidence demonstrated that eyes are a transmission pathway for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The EBAA changed their clinical screening recommendations to be less exclusive by March 2022. 20 Although postmortem testing may be detecting additional COVID-19-positive donors not identified through EBAA clinical screening, given the very low risk of transmission, this benefit is likely negligible 29 and may not be worth the delay to patient care caused by the shortage of corneal tissue, particularly internationally. 35 This study may not be generalizable given the results reflect the experience from 1 eye bank that had a specific protocol for postmortem testing.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of donor-recipient transmission of SARS-CoV-2 is likely very low, as evidenced by numerous studies. 17,18,[29][30][31] In fact, there have been at least 9 corneas transplanted from donors with COVID-19, with no reported transmission. 23 The current EBAA Medical Standards requirement of double povidone-iodine donor preparation is likely viricidal against SARS-CoV-2 within ocular tissue, further limiting the risk of transmission.…”
Section: Discussionmentioning
confidence: 99%